Political Parties Role in Strengthening Democracy in Pakistan - Saiqa Bibi (`, 2025)
Political parties have long been recognized as the backbone of democracy, tasked with representation, policy-making and the development of civic culture. The current paper critically evaluates the complex and paradoxical role of political parties for consolidation of democracy in Pakistan. While parties are a necessary tool for gathering heterogeneous interest groups, promoting constitutional changes like the historic 18th Amendment, and organizing popular participation, their ability is significantly hindered by endemic internal weaknesses. The work critically examines how the personalized nature of dynastic rule, the near total lack of intra-party democracy and the corrosive use of financial patronage and polarization are a deliberate attempt to subvert their democratic potential. The findings indicate that the internal pathologies prevent the development of parties as mature institutions, which in turn gives Pakistani democracy an inherent fragility and renders it more vulnerable to crises. Thus, a necessary condition for achieving democratic consolidation in Pakistan is a radical change in the character of its political parties from personal fiefdoms to programmatic and internally democratic parties. Keywords: Political Parties, Democracy in Pakistan, 18th Amendment, Dynastic Politics, Intra-Party Democracy, Political Polarization, Democratic Consolidation, Institutional Strengthening